Assessment of the barrier function of Chernozem and Luvisol under their experimental contamination by copper ions - A. D. Iovcheva; I. N. Semenkov (Бюллетень Почвенного института им. В.В. Докучаева)
The aim of the work was to assess the ecological resistance of topsoils of Chernozem and Luvisol to modeled copper contamination. To determine the sorption capacity of soils and to obtain the required levels of contamination the experiment was carried out. Soils were contaminated by the Cu acetate solutions with concentrations from 20 to 200 mg/L, which corresponds to the input of 20–2 000 mg/kg of Cu. Approximation of Cu adsorption isotherms by the Langmuir equation was statistically significant. The obtained values of maximum adsorption (Cmax) and Langmuir constant (KL) for Chernozem were higher than for Luvisol. This indicates a higher adsorption capacity and stronger retention of adsorbed Cu in Chernozem compared with Luvisol. This fact can be explained by the higher content and composition of organic matter, the heavier texture and the neutral pH value of Chernozem. By the method of sequential selective extractions, it was found that in uncontaminated soils, more than 50% of Cu is strongly bounded to silicate fraction (>50%). Assessment of Cu fractionation at different levels of contamination reveals a slight increase in the percentage of Cu bioavailable forms (exchangeable and acid-soluble) in Chernozem at 200 mg/kg and its significant increase in Luvisol at 200 mg/kg. At contamination of about 2 000 mg/kg Cu, both soils are characterised by a predominance of pools of bioavailable and bound to (hydr)oxide of Fe and Mn forms. The mobility factor does not exceed 10% for Chernozem and 25% for Luvisol in the native and contaminated by 200 mg/kg soils, which indicates low and medium bioavailability of Cu in them, respectively. Contamination by 2 000 mg/kg of Cu increased the mobility factor up to 25% in Chernozem and up to 40% in Luvisol, which means the medium and high risk of Cu migration into the adjacent environments.